Answer:
w = 6 makes the equation true.
Explanation:
-4w + 8(-2w + 5) = 5(-3w + 2)
Distribute the 8 and the 5.
-4w - 16w + 40 = -15w + 10
Combine like terms.
-20w + 40 = -15w + 10
Add 15w to both sides.
-5w + 40 = 10
Subtract 40 from both sides.
-5w = -30
Divide both sides by -5.
w = 6
Proof:
-4w + 8(-2w + 5) = 5(-3w + 2)
Substitute variable.
-4(6) + 8(-2(6) + 5) = 5(-3(6) + 2)
Multiply inside parenthesis.
-4(6) + 8(-12 + 5) = 5(-18 + 2)
Add inside parenthesis.
-4(6) + 8(-7) = 5(-16)
Multiply.
-24 - 56 = -80
Subtract.
-80 = -80.